374 Effects of maternal nutrition on secretion of leptin in the neonatal heifer and interaction of maternal and postnatal nutrition on age at puberty and postpubertal secretion of luteinizing hormone. (5th December 2019) - O'Neil, Meaghan M; West, Sarah M; Maia, Tatiane S; Cardoso, Rodolfo C; Williams, Gary L
Abstract: Nutrition during gestation and early postnatally can program developmental changes in the offspring that persist until adult life. Here we tested the hypotheses that maternal nutritional during the second and third trimesters of gestation 1) affects neonatal secretion of leptin in heifer offspring, and 2) interacts with dietary energy intake during the juvenile period to affect age at puberty and postpubertal pulsatile secretion of luteinizing hormone (LH) in heifers. Bos indicus-influenced beef cows (n = 108) in 3 replicates bearing heifer fetuses were assigned randomly to receive low (L), moderate (M), or high energy (H) diets to achieve body condition scores (BCS) of 3–3.5 (thin; n = 36), 5.5–6 (moderate; n = 36), or 7.5–8 (obese; n = 36) by the second trimester of gestation until calving. Heifer offspring were weaned at 3–3.5 months of age and assigned randomly to either a high- (H; 1 kg/day) or low-gain (L; 0.5 kg/day) diet for 5 months. Blood samples from a subgroup of 30 heifers (Exp. 1) from cows in each maternal treatment (n = 10/treatment) were collected once every 2–3 days for 2 weeks after birth. In Exp. 2, 18 heifers representing 3 of the maternal × postnatal groups (HH, MH and LL) were ovariectomized and received estradiol replacement (OVX+E) after puberty. Pulsatile secretion of LH was evaluated for 5.5 hours. Maternal nutrition did not affect postnatal circulating leptin. Based on two replicates (n = 61), postnatal diets had the greatest effect on age at puberty (L > H; P < 0.001), with a lesser maternal diet effect (P < 0.10), although LL > HH by 99 days. None of the characteristics of pulsatile LH secretion differed among treatments in OVX + E heifers. Dietary effects on age at puberty were not associated with hormonal characteristics evaluated in these initial studies.